2010
DOI: 10.2337/dc09-2011
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Response Effects of Insulin Glargine in Type 2 Diabetes

Abstract: OBJECTIVETo determine the pharmacokinetic and pharmacodynamic dose-response effects of insulin glargine administered subcutaneously in individuals with type 2 diabetes.RESEARCH DESIGN AND METHODSTwenty obese type 2 diabetic individuals (10 male and 10 female, aged 50 ± 3 years, with BMI 36 ± 2 kg/m2 and A1C 8.3 ± 0.6%) were studied in this single-center, placebo-controlled, randomized, double-blind study. Five subcutaneous doses of insulin glargine (0, 0.5, 1.0, 1.5, and 2.0 units/kg) were investigated on sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 22 publications
6
29
0
4
Order By: Relevance
“…The differences in changes in body weights observed in earlier studies [12][13][14][15]17] in comparison to our present data may be attributed to the different times during the day at which insulin glargine was administered. Lack of significant weight gain in our subjects in Group 2 is likely to be secondary to the administration of insulin glargine in AM as reported in other previous studies [3,[5][6][7][8] whereas the significant weight gain noted in other studies [12][13][14][15]17] may be attributed to bedtime administration of insulin glargine. Weight gain in subjects receiving insulin glargine at bedtime may be due to a consumption of a snack following insulin administration because of the concern of nocturnal hypoglycemia on part of both patients and providers alike especially because of a fairly large dose required by most obese subjects with type 2 Diabetes.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…The differences in changes in body weights observed in earlier studies [12][13][14][15]17] in comparison to our present data may be attributed to the different times during the day at which insulin glargine was administered. Lack of significant weight gain in our subjects in Group 2 is likely to be secondary to the administration of insulin glargine in AM as reported in other previous studies [3,[5][6][7][8] whereas the significant weight gain noted in other studies [12][13][14][15]17] may be attributed to bedtime administration of insulin glargine. Weight gain in subjects receiving insulin glargine at bedtime may be due to a consumption of a snack following insulin administration because of the concern of nocturnal hypoglycemia on part of both patients and providers alike especially because of a fairly large dose required by most obese subjects with type 2 Diabetes.…”
Section: Discussionsupporting
confidence: 70%
“…Weight gain in subjects receiving insulin glargine at bedtime may be due to a consumption of a snack following insulin administration because of the concern of nocturnal hypoglycemia on part of both patients and providers alike especially because of a fairly large dose required by most obese subjects with type 2 Diabetes. Alternatively, a bedtime snack is not advised and frequently not consumed by subjects on AM administration of insulin glargine because of a distinctly less concern of nocturnal hypoglycemia on part of both patients and providers since nocturnal hypoglycemia is significantly less frequently documented in studies using insulin glargine in AM [3,[4][5][6][7][8]. Thus, the difference in total daily caloric consumption may contribute to these different outcomes regarding body weights in subjects receiving insulin glargine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, an indirect comparison of PK and PD between studies, where glargine was given in the evening (14) compared with the morning (15)(16)(17), suggests important differences in action profiles, although in such a comparison the contribution of circadian changes in insulin sensitivity should be taken into account (18,19).…”
mentioning
confidence: 99%
“…A systematic review by Wang et al showed that insulin glargine is effective in the management of T1DM and provides consistent insulin delivery which ensures effective glycemic control for 24 hours making it suitable for once daily dosing [15].…”
Section: Introductionmentioning
confidence: 99%